Tuning the bonding dimensions for coordination polymers based on rare earth metal ions. Issue 42 (12th October 2022) - Zhou, Juan; Yu, Wanting; Tang, Sisi; He, Xiaomin; Zhang, Xinlei; Zhou, Lian; Sun, Lin; Zhang, Jun
Abstract : The micro dimensions for the coordination polymers (CPs), namely, 1D chain (compound 1 ), 2D sheet (compound 2 ), and 3D skeleton (compound 3 ), were constructed from Eu 3+, Ho 3+, and Tb 3+, respectively, coordinating with the same ligand. Abstract : The structures of targeted coordination polymers (CPs) are strongly affected by various factors: ligands, ions, and synthetic conditions. Herein, rare earth metal ions, namely, Eu 3+, Ho 3+, and Tb 3+, were introduced into the synthesis, constructing micro bonding frameworks with 1D chains (compound 1 ), 2D sheets (compound 2 ), and 3D skeletons (compound 3 ), respectively. Compounds 1 and 3 exhibit the characteristic photoluminescence emission for the rare earth metal ions.